2010
DOI: 10.1038/nphoton.2009.269
|View full text |Cite
|
Sign up to set email alerts
|

Laser cooling of solids to cryogenic temperatures

Abstract: Laser radiation has been used to cool matter ranging from dilute gases to micromechanical oscillators. In Doppler cooling of gases, the translational energy of atoms is lowered through interaction with a laser field(1,2). Recently, cooling of a high-density gas through collisional redistribution of radiation has been demonstrated(3). In laser cooling of solids, heat is removed through the annihilation of lattice vibrations in the process of anti-Stokes fluorescence(4-6). Since its initial observation in 1995, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
232
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(241 citation statements)
references
References 27 publications
8
232
1
Order By: Relevance
“…[3][4][5][6][7][8][9] UC refers to an anti-Stokes type nonlinear optical emission process in which one higher energy photon is emitted for every two or more absorbed lower energy photons. 10 Since the first experimental demonstration in 1966, 11 this effect has received renewed interest due to its ever expanding application base in, for example, lasing, 12 laser cooling, 13 temperature sensing, 14 biomedical imaging and therapy, 15,16 3D displays, 17 and, more recently, for broadening the spectral response of PV devices. [4][5][6][7][8][9] In the context of Si PV devices, the UC of the sub-bandgap photons (k > 1100 nm) into above-bandgap photons (k < 1100 nm) increases the theoretical efficiency limit of a single-junction Si solar cell from near 30% up to 40% when illuminated under non-concentrated light.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] UC refers to an anti-Stokes type nonlinear optical emission process in which one higher energy photon is emitted for every two or more absorbed lower energy photons. 10 Since the first experimental demonstration in 1966, 11 this effect has received renewed interest due to its ever expanding application base in, for example, lasing, 12 laser cooling, 13 temperature sensing, 14 biomedical imaging and therapy, 15,16 3D displays, 17 and, more recently, for broadening the spectral response of PV devices. [4][5][6][7][8][9] In the context of Si PV devices, the UC of the sub-bandgap photons (k > 1100 nm) into above-bandgap photons (k < 1100 nm) increases the theoretical efficiency limit of a single-junction Si solar cell from near 30% up to 40% when illuminated under non-concentrated light.…”
Section: Introductionmentioning
confidence: 99%
“…30 In 2010, Seletskiy et al, reported laser cooling of ytterbium doped glasses to 110 K from room temperature. 31 Semiconductors are also attractive and promising materials for optical refrigeration. [32][33][34][35] One of the most intensively studied semiconductor devices for optical refrigeration are GaAs based quantum wells, whose EQE can be as high as 99.5%.…”
Section: Optical Refrigerationmentioning
confidence: 99%
“…31,38 Therefore, η abs and η EQE have to be closed to unity to guarantee an η c > 0. The requirement for EQE can be lower for electroluminescent cooling because η elec = ω qV can be arbitrarily high by applying low voltage.…”
Section: Optical Refrigerationmentioning
confidence: 99%
“…[1][2][3] Ideally, the high IQE is expected to enable electroluminescent (EL) cooling 4,5 if the high IQE can be converted to a high external quantum efficiency (EQE) by very efficient light extraction or by adopting thermophotonic (TPX) approaches where the light is absorbed within the semiconductor material. 6 While EL cooling at technologically relevant power levels is yet to be demonstrated, the expectations for functional thermophotonic coolers have very recently been reinforced by the progress and first demonstrations of optical refrigeration in doped glasses 7,8 and II-IV compound semiconductors 9 as well as the demonstrations of very low power EL cooling in GaSb/InGaAsSb LEDs. 10,11 Although the first EL cooling demonstrations took place under very low bias voltages, they demonstrated electricityto-light conversion efficiencies exceeding unity by a large margin.…”
Section: Yield and Leakage Currents Of Large Area Lattice Matched Inpmentioning
confidence: 99%